The Delft Innovation Method : a design thinker's guide to innovation - Buijs, Jan, ....- (The Hague : Eleven International Publishing, 2012)
This book deals with the process that leads to innovations. It provides an overall method for innovating in companies. As the method originated in Delft, it is called The Delft Innovation Method, and it consists of five interconnected elements: 1) a general model of the corporate innovation process; 2) a facilitative leadership style; 3) a diversely composed innovation team; 4) the use of creative techniques; and 5) the connection of the company to the external world. The Delft Innovation Method is written in a basic style with clarifying examples and illustrations. It starts a learning process on corporate product- and service-innovation. The metaphor of going on an 'innovation country tour of discovery' is used for structuring the book. It offers a general description of the future innovation country, a detailed roadmap of that country, and details are given about how to organize for this trip and how to find fellow travelers.
Includes bibliographical references.
Keywords: Technological innovations -- Management